The National Health Service - Great Britain. Central Office of Information. (London : His Majesty's Stationery Office, 1948)
1948 1948 1940s 38 pages 2 THE NEW HOSPITAL AND SPECIALIST SERVICES UNTIL 5th July, 1948, there were over 1,000 independent voluntary bodies providing hospitals, and an even greater number of separate local authorities with powers to provide hospitals of one kind or another. The fourteen large new regions are each linked with a university with one or more medical schools and one or several teaching hospitals, and each regional hospital board controls the great majority of the former voluntary and municipal hospitals within the region, with their associated clinics and specialist services — but not the teaching hospitals, each of which retains its own governing body. Under the general guidance of the regional boards the hospitals are managed, singly or in convenient groups, by management committees appointed by, and responsible to the boards. The number of these new committees varies in each region from fifteen to sixty according to the size and circumstances of the region. The patient is not tied to the hospitals of his own region, though most regions will tend more and more to be self-sufficient as time goes on. The hospital service is a single system for the whole country ; the regions are for convenience of management. Each region has its intellectual centre for medical work in a city with a university medical school. Wherever possible it is also the natural 'catchment area' within which patients needing special treatment would usually be referred from a small local hospital to a larger centre. On the average the regions have a population of about three million, but the size varies with geographical and other factors. For example most of the north-west of England with 4,400,000 people falls within the Manchester region ; Wales has 2,500,000 people, while the Liverpool region, between the two, has only 1,800,000. But Wales has only 23,000 hospital beds, while Liverpool has 30,000 and will of course continue to serve North Wales. In south-east England, where 12,700,000 people are served by hospitals centring on London, four Metropolitan regions have been created, each containing a quarter of London and running out into 9 21/1489